Effect of injection position on throttle body injection mixer for compressed natural gas motorcycle - Chang, Yvonne S. H.; Yaacob, Zulkefli; Mohsin, Rahmat; Abdul Majid, Zulkifli (2005)

(untitled)
A good gaseous mixer must be able to prepare a homogeneous mixing of air and fuel at a specific air- fuel ratio prior to entering the engine in order to avoid low fuel efficiency and high exhaust emissions. Thus, effect of injection position on the mixing in Throttle Body Injection Mixer (TBIM) for a compressed natural gas (CNG) motorcycle was investigated in this work through Computational Fluid Dynamics (CFD) modeling. The aim of CFD modelling was to study the effect of various injection positions on the mixing in TBIM which otherwise was not available visually through experimental work. The optimum injection position throughout the case studies was also investigated in this work. CFD results revealed a significant effect of various injection positions on the hydrodynamics of air and in TBIM. Injection position is therefore a fundamental parameter for the mixing in TBIM.